Reaktivní lymfoidní hyperplazie jater - Dobiašová, B; Zvaríková, M; Petráková, K (Klinicka onkologie, 2017)
Here, we present the case of a 50-year-old woman diagnosed with stage I hormone-dependent breast cancer. The patient underwent partial mastectomy followed by adjuvant radiotherapy and hormone treatment with tamoxifen. Three years later, she presented with a solitary liver lesion on MRI, which was highly suspicious of malignancy. However, several fine needle biopsies were performed, and histopathological examination revealed no signs of neoplasia. As a result of these alarming discrepancies, the multidisciplinary board recommended a diag-nostic laparotomy, which yielded a finding consistent with reactive lymphoid hyperplasia, a pseudolymphoma of the liver, on a background of incipient steatohepatitis. This rare condition is characterized by proliferation of non-neoplastic lymphocytes in extranodular sites, and is usually an incidental finding on imaging modalities in clinically asymptomatic patients, predominantly women. Lesions share some radiologic features with primary malignant liver diseases such as hepatocellular carcinoma or cholangiocarcinoma. Although the etiology remains unclear, reactive lymphoid hyperplasia is believed to be associated with some malignancies, including breast cancer, or inflammatory and autoimmune disorders. Reactive lymphoid hyperplasia usually progresses slowly, with some cases of spontaneous regression described in the literature. To the best of our knowledge, only 50 cases of hepatic reactive lymphoid hyperplasia have been reported so far.Key words: pseudolymphoma - hyperplasia - liver - lymphatic tissue The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 20. 3. 2017Accepted: 10. 4. 2017.
Keywords: nádory prsu; Female; laparotomie; pseudolymfom; Breast Neoplasms; mastektomie; Humans; ženské pohlaví; Laparotomy; lidé; Middle Aged; lidé středního věku; Mastectomy; Pseudolymphoma